Does Internal and External R&D Affect SMEs Innovation Performance? Micro Level Evidence from India and Pakistan - Naqeeb Ur Rehman (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The purpose of this study is to investigate the impact of internal and external R&D on SMEs innovation performance. Micro level data was obtained from Enterprise Survey. For analysis, bivariate models have been used. The results show that internal and external R&D positively affects the product and process innovations. However, this effect is stronger for Indian SMEs. In comparison, only external R&D showed positive association to product and process innovation for Pakistani SMEs. Similarly, Pakistani SMEs are externally constrained (lack of access to credit) than Indian SMEs. Moreover, Indian SMEs are dominant in terms of undertaking internal R&D, generating product and process innovations than Pakistani SMEs. Lastly, the complementary relationship has been examined between internal and external R&D for both countries. Regarding contribution, this research study for the first time has examined the Indian and Pakistani SMEs innovation activities. The implication of this study suggests that business managers can utilize the balance combination of internal and external R&D to accelerate the SMEs innovation performance.
Additional information: Dr. Naqeeb has received his PhD in economics from University of Glasgow in 2012. He is active researcher related to SMEs productivity and innovation. Presently, he is working as researcher at Hazara University Mansehra, Pakistan.
Keywords: O3; 330; Internal and External R&D; SMEs; Innovation; SME